“The Key to it All”: Why Are We Obsessed with Ishmael, and Are Likely to Continue to Be Obsessed with Him? - Giorgio Mariani (European journal of American studies, 2023)
Rather than focusing on Ahab’s or Ishmael’s obsession with the White Whale, in my essay I wish to explore the reasons why critics have become obsessed with Ishmael. This critical obsession began to emerge in the 1940s, after the Melville Revival, when, as Clare Spark has shown, critics were mostly “Ahab-obsessed.” The emergence of Ishmael-centric readings of Moby-Dick is usually connected to the rise of the Cold War, but I intend to suggest that—important as the search for a cultural consensus engendered by the aftermath of the war undoubtedly was—other factors help explain the critics’ understanding of Moby-Dick as, primarily, “Ishmael’s mighty book.” In particular, the concurrent rediscovery of Henry James’s aesthetics of the novel explains why critical attention shifted to the narrator’s perspective, ideologically constructed as a space of “freedom.” But while, for the most part, I employ the term ‘obsession’ in its commonsensical meaning of being intensely preoccupied with someone or something, in the last part of my essay the etymology of the term also comes into play. The word derives from the Latin obsessio, the past-participle stem of obsidere, “to besiege.” So, obsession can also be understood as a siege, a blockade. Indeed, of late, for some critics Ishmael has become a sort of obstacle to the proper understanding of the text. The “discovery” of Ishmael in the 1940s and especially the 1950s seems to have solved a number of both formal and ideological problems. Yet nowadays not only have some readers (usually identified as the New Americanists) themselves “besieged” Ishmael both as character and narrator, but others have actually sought, if not to get rid of him altogether, then to demote him to a figure of secondary importance. The story I wish to tell reveals that the recently much debated dichotomy between “ideological” and more “personal” reading may ultimately be untenable.